Anomaly in Supervision of MSME Partnerships in Indonesia: A Comparison of Indonesia, Malaysia, and Vietnam - Hadyan Yunhas Purba, M.; Natasya Sirait, Ningrum; Siregar, Mahmul; Harianto, Dedi (KnE Social Sciences, 2024)
Partnership for micro, small, and medium enterprises (“MSMEs”) is a strategy to improve the quality of MSMEs through sharing knowledge and technology, funding, etc. Therefore, Law No. 20/2008 jo. Government Regulation No.7/2021 regulates the implementation of MSME partnerships. One of them is related to the Supervision of MSME Partnerships carried out by the Business Competition Supervisory Commission “(KPPU”). This study aims to test whether the KPPU’s authority to oversee MSME partnerships is appropriate or not. By compiling a list of laws and regulations, journals, and other materials, this study employs a normative juridical methodology. The data obtained will be analyzed qualitatively by concluding inductively. As a result, the supervision of MSME partnerships by KPPU does not follow the basis and objectives of the establishment of KPPU. Compared to Malaysia, all MSME development activities are regulated and supervised by SME Corporation Malaysia (SME Corp. Malaysia) as an authority under the Ministry of Entrepreneur Development and Cooperatives (“MEDAC”). Meanwhile, in Vietnam, the Government established The Vietnam Trade Promotion Agency (VIETRADE) which is under the Ministry of Industry and Trade of Vietnam with one of the tasks of its authority to develop MSMEs and encourage MSME cooperation with large companies. Seeing this comparison, it is appropriate that the authority to manage all MSME activities including partnerships is given to an institution whose main focus is handling the MSME sector in Indonesia, namely the Ministry of Cooperatives and SMEs. Keywords: supervision, MSME partnerships, comparison